Investigation of spin-orbit torque performance with W/Cu-multilayers as spin current source - Coester, Birte (2023)
We study the W/Cu multilayers as a spin current source and the coherent spin-orbit torques in a Fe layer using the spin-torque ferromagnetic resonance (STFMR) technique. With increasing numbers of layers, the line shape of the STFMR signals changes from predominantly antisymmetric to predominantly symmetric. When using [W(0.5)/Cu(0.5)]5 as a spin current source, the symmetric amplitude increases by a factor of 5 compared to a single W layer. Simultaneously, the effective damping parameter also increases slightly due to enhanced spin pumping. Along with an increasing trend in the damping-like torque efficiency, this suggests that the extrinsic spin Hall effect is enhanced. Concurrently, the antisymmetric amplitude decreases significantly by a factor of 27, which indicates an increase in the field-like torque when multilayers are used as a spin current source.